Life-cycle stock market participation in taxable and tax-deferred accounts - Zhou, Jie. (2013)
The stock market participation patterns differ significantly in taxable (TAs) and tax-deferred accounts (TDAs). This paper develops a quantitative life-cycle model to study the optimal stock market participation choice for households with assets in both TAs and TDAs. We find that differential costs of stock market participation in the two accounts explain the higher participation rate in TDAs early in life relative to TAs and the increasing stock market participation rate in TAs over the life cycle. We also show that the differential tax treatment between TAs and TDAs is responsible for the decline in the participation rate in TDAs late in life, while the basis-reset provision of the tax code is not quantitatively important.